2014
DOI: 10.1016/j.econmod.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Causal interactions between CO2 emissions, FDI, and economic growth: Evidence from dynamic simultaneous-equation models

Abstract: In this article, we investigate the causality links between CO2 emissions, foreign direct investment, and economic growth using dynamic simultaneous-equation panel data models for a global panel of 54 countries over the period 1990-2011. We also implement these empirical models for 3 regional sub-panels: Europe and Central Asia, Latin America and the Caribbean, and the Middle East, North Africa, and sub-Saharan Africa. Our results provide evidence of bidirectional causality between FDI inflows and economic gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
207
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(256 citation statements)
references
References 56 publications
(51 reference statements)
18
207
2
2
Order By: Relevance
“…In a sectoral level (fishing and agriculture) analysis on OECD countries, Pazienza (2015) indicates that FDI has a negative effect on CO2 emissions. On contrary, in a comprehensive analysis which involved data on 54 countries, 5 Omri et al (2014) highlight the existence of a feedback effect between FDI and CO2 emissions, except in Europe and North Asia. Their findings strongly imply that one shall consider the regional-level and country-level heterogeneities, while analysing the nexus between FDI and emissions.…”
Section: Fdi-emissions Nexusmentioning
confidence: 96%
“…In a sectoral level (fishing and agriculture) analysis on OECD countries, Pazienza (2015) indicates that FDI has a negative effect on CO2 emissions. On contrary, in a comprehensive analysis which involved data on 54 countries, 5 Omri et al (2014) highlight the existence of a feedback effect between FDI and CO2 emissions, except in Europe and North Asia. Their findings strongly imply that one shall consider the regional-level and country-level heterogeneities, while analysing the nexus between FDI and emissions.…”
Section: Fdi-emissions Nexusmentioning
confidence: 96%
“…Most of the studies in the literature [Shahbaz et al (2015), Kivyiro and Arminen (2014), Omri, Nguyen and Rault (2014), Blanco, Gonzalez and Ruiz (2011) (Tang and Tan (2015), Asghari (2013), Öztürk and Öz (2016), Atay Polat (2015), Şahinöz and Fotourehchi (2014)] show that FDI reduce CO2 emissions. Some of the studies [Keho (2016), Kim and Adilov (2012), Zeren (2015)] have found both positive and negative results depending on the countries included in the analysis.…”
Section: Pollution Halo Hypothesismentioning
confidence: 99%
“…Although numerous time series and panel studies have examined such associations (e.g., Omri et al, 2014;Ozcan, 2013;Ozturk & Acaravci, 2011), to the best of the authors' knowledge, no study has yet been undertaken to determine such causal relationships in the context of Kuwait, which is potentially a very important country for such investigation. The current study is an attempt to fill this gap.…”
Section: Introductionmentioning
confidence: 99%